Let's break down the problem step by step.
- Let \( a \) be Tony's current age.
- Since Andrea is 6 years younger than Tony, we can express Andrea's age as \( a - 6 \).
- In 2 years, Tony's age will be \( a + 2 \) and Andrea's age will be \( (a - 6) + 2 = a - 4 \).
- According to the problem, in 2 years, Tony will be three times as old as Andrea, which gives us the equation: \[ a + 2 = 3(a - 4) \]
Now, let's check which of the options corresponds with the correct equation:
-
Option 1: \( a + 2 = 3(a - 6 + 2) \)
- This simplifies to \( a + 2 = 3(a - 4) \) (which is correct).
-
Option 2: \( a + 2 = 3(a + 6 + 2) \)
- This is incorrect. It suggests that Andrea is older than Tony.
-
Option 3: \( 3(a + 2) = a - 6 + 2 \)
- This is incorrect because it doesn't represent the relationship properly.
-
Option 4: \( a = 3(a + 2) \)
- This is incorrect because it does not accurately represent the age relationship.
The correct response is that the equation that can be used is:
Option 1: \( a + 2 = 3(a - 6 + 2) \).